Technology in the classroom : EFL teachers' technological pedagogical and content knowledge = Tehnologija u razredu : tehnološka pedagoška i sadržajna znanja učitelja EFL-a - Mukminin, Amirul (Array, 2020)
This is a mix-method study with a sequential explanatory design aimed at investigating the level of technology knowledge of EFL teachers in Indonesian senior high schools. In this study, a total number of 375 teachers from public schools located in the southern part of Sumatra Island, Indonesia, were voluntarily involved in the survey. To fit the context of the study, the TPACK survey was adapted from previous literature with the overall Cronbach’s alpha ranging from .82 to .89. The adapted instruments were validated through content validity involving four experts in educational technology and one expert of English-Indonesian language translation. We also applied Cronbach’s alpha testing, the reliability of the adapted instruments (0.75 to .89). Mean and p-value were reported in the quantitative report. Afterward, we interviewed teachers using semi-structured interview which questions were based on the survey items. The data were transcribed, translated, coded, and put into themes. Findings showed that all teachers had more knowledgeable of traditional, non-technological conception of pedagogy, and content than technological pedagogy and technological content.